2005
DOI: 10.5507/bp.2005.048
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Conversion Study of a New Cyclosporine Formulation in Stable Adult Renal Transplant Recipients

Abstract: Cyclosporine A (CyA) is a standard component of immunosuppressive regimens. It is a critical-dose drug for which a minor change in absorption can have important clinical consequences. The aim of the study was to compare the pharmacokinetics and safety of the new generic CyA formulation, Equoral ® capsules, after a switch from original formulation, Neoral ® capsules, in seventy stable adult renal transplant recipients. The extent and rate of pharmacokinetic parameters for bioequivalence were compared in a non-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Table provides the tabulation of the reported C max and AUC values from the various patient studies and healthy subject clinical pharmacology studies reported in the literature . The prediction of AUC values for cyclosporine was performed using the regression equation: AUCitaliccyclosporine0.25em=italicCmaxitalicCyclosporine0.25em×0.25em3.99650.25emprefix+384.5 and the appropriate fold differences were computed (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Table provides the tabulation of the reported C max and AUC values from the various patient studies and healthy subject clinical pharmacology studies reported in the literature . The prediction of AUC values for cyclosporine was performed using the regression equation: AUCitaliccyclosporine0.25em=italicCmaxitalicCyclosporine0.25em×0.25em3.99650.25emprefix+384.5 and the appropriate fold differences were computed (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…5 In that study, the authors reported a higher rejection rate among Equoral users compared with users of the innovator drug. 5 On the basis of published pharmacokinetic data on healthy individuals 6 and on de novo 7 and long-term transplant patients, 8,9 it is hard to corroborate that the high rejection rate in that uncontrolled and flawed trial is related to the generic CsA Equoral. In summary, considering the comparable CsA dose and the comparable CsA trough levels of both cyclosporine formulations in our study, the data presented here support the assumption that both are interchangeable.…”
Section: Discussionmentioning
confidence: 98%
“…In patients after renal transplantation, promising study data are available, showing comparable daily cyclosporine doses and levels after the switch to a generic CSA, without significant differences regarding adverse events 7. However, available study data in patients after HTx are extremely limited.…”
Section: Discussionmentioning
confidence: 99%